Influenza Vaccine With Consensus Internal Antigens as Immunogens Provides Cross-Group Protection Against Influenza A Viruses - Xie, Xinci; Zhao, Chen; He, Qian; Qiu, Tianyi; Yuan, Songhua; Ding, Longfei; Liu, Lu; Jiang, Lang; Wang, Jing; Zhang, Linxia; Zhang, Chao; Wang, Xiang; et al. (Frontiers in Microbiology, 2019)
Given that continuing antigenic shift and drift of influenza A viruses result in the escape from previous vaccine-induced immune protection, a universal influenza vaccine has been actively sought. However, there were very few vaccines capable of eliciting cross-group ant-influenza immunity. Here, we designed two novel composite immunogens containing highly conserved T-cell epitopes of six influenza A virus internal antigens, and expressed them in DNA, recombinant adenovirus-based (AdC68) and recombinant vaccinia vectors, respectively, to formulate three vaccine forms. The introduction of the two immunogens via a DNA priming and viral vectored vaccine boosting modality afforded cross-group protection from both PR8 and H7N9 influenza virus challenges in mice. Both respiratory residential and systemic T cells contributed to the protective efficacy. Intranasal but not intramuscular administration of AdC68 based vaccine was capable of raising both T cell subpopulations to confer a full protection from lethal PR8 and H7N9 challenges, and blocking the lymphatic egress of T cells during challenges attenuated the protection. Thus, by targeting highly conserved internal viral epitopes to efficiently generate both respiratory and systemic memory T cells, the sequential vaccination strategy reported here represented a new promising candidate for the development of T-cell based universal influenza vaccines.